Formation model of sound engineers’ communicative competence - Yuriy A. Kachalov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper considers the concept of communicative competence of a sound engineer. The importance of communications in the professional activity of a sound engineer is revealed. Theoretical and methodological approaches to the concept of communicative competence are analyzed. The role of the personality-oriented approach in the formation of communicative competence is determined. The paper proposes a model for the formation of communicative competence of future sound engineers on the basis of the personality-oriented approach. The model consists of 4 blocks: aim, methodology, content and evaluation of the results. The blocks clearly distribute the methodological and methodical aspects of achieving the set goal. The components of communicative competence of sound engineers are presented, in accordance with them, teaching methods are selected within the framework of the personality-oriented methodology. At the same time, due to the expansion of subjective experience, the use of self-analysis and empathy, the development of student personality is additionally stimulated. Using the program, the teacher can implement the proposed methods or adapt their own professional and communicative experience within the framework of the formation of a specific component of communicative competence of sound engineers. This makes it possible to approach the improvement of communication skills of students with different levels of communicative competence more flexibly. The principles of implementing the model in the learning process are outlined. The structure of the course «Professional Communications of sound engineers» is compiled. The methods aimed at obtaining and consolidating the basic theoretical information necessary for understanding the work of communication processes in the work of a sound engineer are described. The paper consistently reveals the methodology of forming the functional components of communicative competence by applying personality-oriented teaching methods. The research also analyzes the use of active and interactive teaching methods in the context of personality-oriented methodology. The most important condition for implementing the model for forming the communicative competence of sound engineers is considered: training of teachers to apply the personality-oriented approach.